The Glyptothorax of Sundaland: a revisionary study (Teleostei: Sisoridae) - Ng, Heok Hee; Kottelat, Maurice (Zootaxa, 2016)
The species of Glyptothorax of Sundaic Southeast Asia (Malay Peninsula, Sumatra, Borneo and Java) are revised in this study. A total of 17 species are recognized, of which six (G. amnestus, G. decussatus, G. famelicus, G. keluk, G. pictus and G. stibaros) are described as new here. A lectotype is designated for G. platypogon. The Sundaic Glyptothorax species are diagnosed by combinations of color pattern, morphometry (with particular regard to the eye, head, body depth, and caudal peduncle), dorsal-spine and thoracic adhesive apparatus morphology.